Consolidated quality improvements following benchmarking with cardiothoracic surgery registries—a systematic review. (6th December 2019) - de By, Theo M M H; Muslem, Rahatullah; Caliskan, Kadir; Bortolussi, Giacomo; Philipsen, Tine; Friberg, Örjan; Bogers, Ad J J C; Pagano, Domenico
Abstract: The influence of registries in medicine is large. However, there has been no systematic assessment conducted to quantify the impact of benchmarking with registries focused on cardiothoracic surgery. Numerous publications conclude that registry participation leads to improvement of outcomes for patients. A large number of registries provide evidence sub-structured by statistics that show decreases in morbidity and mortality in the participants' clinical units. Many authors praise the benchmarking method making use of databases of registries as having a positive effect on outcome of care. However, studies proving the direct causal relation between the use of cardiothoracic surgery-oriented registries and improvement of clinical in-hospital outcomes are extremely scarce. We aimed to analyse the causal relation between the use of cardiothoracic surgery-oriented registries and improvement of clinical outcomes. In a systematic literature review, publications demonstrating the use of registry data to obtain consolidated quality improvements were selected. After analysis of 2990 scientific publications, 6 studies filled the inclusion criteria. The selected studies acknowledged that benchmarking of data against registries was used for a focused and methodologically organized improvement in cardiothoracic departments. In conjunction with the impact of the applied methods on healthcare, their results demonstrate quantifiable enhanced local outcomes over time.